Legislation of Accounting in the Republic of Bulgaria in the Years of Transition - Basheva, Snejana; Pozharevska, Rumiana (Research Papers, 2023)
The object of research in the report is the organization and the normative framework of accounting in the Republic of Bulgaria after the democratic changes in 1989. The positive and negative tendencies in the period 1991 – 2021 are analyzed in retrospect.
Keywords: Normative framework; Organization of accounting in the Republic of Bulgaria; Accounting